Study on Influcing Factors for Reduction Capacity of Gray-Green Sandstone in Ordos Sandstone-type Uranium Deposits - ZHANG Li-juan; AN Shu-qing; XU Tie-min; ZHANG Nan; WEI Shuang; FANG Peng-da (Yankuang ceshi, 2018)
BACKGROUND The reductive environment of uranium is the most important influencing factor of uranium mineralization. The study of various redox markers in interlayer oxidation bands is of great significance for finding interlayer oxidation zone sandstone-type uranium deposits. OBJECTIVES The reduction experiments were carried out on reducing materials commonly found in sandstone-type uranium deposits such as ferrous, sulfide, pyrite, ilmenite, humic acid, biogas, and hydrogen. The reduction capacity of ferrous ion, sulfur ion, pyrite and other reduction factors at room temperature and pressure was studied. METHODS By polarography and spectrophotometry experiments to determine U(Ⅵ) and U(Ⅳ) content respectively. Their reduction capacity was analyzed. RESULTS Iron ion and sulfur ion had strong reducing properties, andhumic acid had certain reducing properties. Such as pyrite, ilmenite experiment in different acidity and sage green sandstone water soaking experiments showed that the soaked solution of gray-green sandstone contained a certain amount of ferrous ions, and there was no sulfur ion. CONCLUSIONS These ferrous ions were the main reason for the strong reducibility of gray-green sandstone. It also indicated that the gray-green sandstone was one of the most important factors in the subsequent mineralization of sandstone type uranium deposit in Ordos area.